PENGARUH PENGGUNAAN HANDPHONE TERHADAP MINAT MEMBACA BUKU PELAJARAN PADA PESERTA DIDIK KELAS V DI SD NEGERI 3 PANJER - Goreti Rini Kristiantari, Maria; Chindytia, Chindytia; Diantari Widana, Ni Made; Triani Prashanti, Ni Komang; Ayu Nirmala Sari, Ni Putu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to analyze the impact of cell phone use on the reading habits of fifth-grade students at SD Negeri 3 Panjer. This study employed a quantitative approach with a correlational research design. A total of 28 students were selected as research subjects using a saturation sampling technique. The data were analyzed using a Likert-scale questionnaire, which was then evaluated using simple linear regression analysis, t-tests, and the coefficient of determination. The findings indicate a negative correlation between cell phone use and reading interest, although this correlation is not statistically significant. This is supported by a significance level of 0,145 > 0,05 and a calculated t-value (-1,503) that is smaller than the critical t-value (2,056). Furthermore, the coefficient of determination (R²) of 0,080 indicates that the variable of cell phone use accounts for only 8% of the variation in reading time, while the remaining 92% is determined by other variables not included in this study. Consequently, cell phone use is not a dominant factor influencing students’ reading habits.